(untitled) (International Journal on Stereo & Immersive Media, 2021)
The recent surge in popularity of video games has allowed for a deeper understanding and analysis of how video games can create powerfully immersive experiences. The blending of music and sound with the interactive and reactive nature of gameplay provide an experience that draws players into these gameworlds. A striking example of this effect can be seen in the game ‘Crypt of the Necrodancer’. Music is used as a controlling element that reinforces the transportational sense of player immersion. The player is restricted to only move to the beat of the soundtrack. All gameplay and musical elements respond and move in time to the music, resulting in the player ‘dancing’ around the levels. Isabella Van Elferen’s (2016) ALI methodology is used to break down and examine key aspects of the game and its music by drawing connections between the gameplay mechanics and the audio design.